Interdependencies in the Energy-Bioenergy-Food Price Systems: A Cointegration Analysis - Pavel Ciaian; d'Artis Kancs (Economics and Econometrics Research Institute (EERI), 2009)
The present paper examines a long-run relationship between the energy, bioenergy and food prices. In the recent years the bioenergy production has increased significantly around the world. The increase has been driven by rising energy prices as well as by environmental policies aiming at reducing the harmful effects of conventional sources of energy, such as climate change. Bioenergy, in turn, affects agricultural markets, because it uses agricultural commodities as inputs. The theoretical model we develop predicts that, because of price inelastic food demand, the agricultural price increase may be substantial. The empirical findings confirm the theoretical hypothesis that energy prices do affect prices of agricultural commodities. However, the co-integration is weaker than theoretically predicted. The price effect of bioenergy might be mitigated by new technological development, which improve yields and lead to an offsetting effect in the supply of agricultural commodities, and by fallow land brought into cultivation, when agricultural profitability is rising.
Keywords: Q11; Q13; Q42; 330; Energy; bioenergy; crude oil; prices; cointegration